Analisis Kebutuhan Media Pembelajaran Berbasis Multimedia Interaktif pada Materi Statistika Kelas VIII SMP - Annisa Maiyada; Mulia Putra; Hendra Kartika (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2026)
Statistics learning at the junior high school level still faces challenges that affect students’ low interest and learning motivation; therefore, learning media that align with students’ characteristics are needed. This study aims to analyze the needs for interactive multimedia-based mathematics learning media on statistics material. This research is a preliminary study within the Research and Development (R&D) framework, focused on the Analysis stage. The study was conducted at SMP Negeri 1 Klari, Karawang Regency. The research subjects involved in the interview activities consisted of one mathematics teacher and three eighth-grade students selected using purposive sampling based on high, medium, and low academic ability levels as determined by the teacher’s assessment. Meanwhile, observation activities were conducted in one eighth-grade class to observe the implementation of mathematics learning in the classroom. Data were collected through interviews and observations, then analyzed using descriptive qualitative methods through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that statistics learning is still dominated by lecture-based methods using traditional media, while the utilization of digital media in the form of applications remains limited. The needs analysis findings suggest that the required media are interactive multimedia-based learning applications characterized by attractive visual displays, contextual presentation of materials, integration of videos and animations, and equipped with interactive practice questions and instant feedback. In addition, students showed a high preference for digital media that can be accessed independently. These findings serve as the basis for designing interactive multimedia learning media in the subsequent development stage.